2016
DOI: 10.5194/tc-2016-115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and analysis of a continuous record of global near-surface soil freeze/thaw patterns from AMSR-E and AMSR2 data

Abstract: Abstract. Monitoring near-surface soil freeze/thaw patterns is becoming essential under the context of global changes as it is more sensitive to climatic fluctuation compared with subsurface thermal characteristics and its 15 evolution could be an early warning of changes in near-surface permafrost. It requires continuous long term and stable data record for understanding hydrological, ecological and biogeochemical responses of permafrost to global climate change. AMSR2 (Advanced Microwave Scanning Radiometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It also has the highest accuracy compared with two other algorithms, dual index [9] and decision tree algorithm [11], when applied to AMSR-E data [22]. In addition, further validation of this algorithm was conducted in our previous work using in situ air temperature measurements from the World Meteorological Organization (WMO, 88.37% and 82.76% for observations at 1:30 and 13:30, respectively), 0-5 cm soil temperature from International Soil Moisture Network (ISMN, 86.63%), as well as modelled soil temperature by the Global Land Data Assimilation System (GLDAS, 89.74% and 87.6% for observations at 1:30 and 13:30, respectively) [23]. A brief introduction of DFA is presented here.…”
Section: Discriminant Function Algorithm (Dfa)mentioning
confidence: 99%
See 1 more Smart Citation
“…It also has the highest accuracy compared with two other algorithms, dual index [9] and decision tree algorithm [11], when applied to AMSR-E data [22]. In addition, further validation of this algorithm was conducted in our previous work using in situ air temperature measurements from the World Meteorological Organization (WMO, 88.37% and 82.76% for observations at 1:30 and 13:30, respectively), 0-5 cm soil temperature from International Soil Moisture Network (ISMN, 86.63%), as well as modelled soil temperature by the Global Land Data Assimilation System (GLDAS, 89.74% and 87.6% for observations at 1:30 and 13:30, respectively) [23]. A brief introduction of DFA is presented here.…”
Section: Discriminant Function Algorithm (Dfa)mentioning
confidence: 99%
“…Although AMSR-E and AMSR2 have been reported to have slight differences [29,30], eliminating the difference is still necessary through inter-calibration before applying the same algorithm (e.g., DFA) to observations of these two sensors [31]. The data of AMSR2 used in this study have been calibrated with AMSR-E without many details being obtained [23]. The high-resolution F/T maps also depend significantly on thermal observations, especially the spatial resolution.…”
Section: High-resolution F/t Mapsmentioning
confidence: 99%
“…A lot of studies have demonstrated that microwave remote sensing is feasible for freeze/thaw state estimation including passive and active sensors with various temporal and spatial resolutions. Space‐borne radiometers such as the scanning multichannel microwave radiometer (SMMR) [ Zuerndorfer and England , ], Special Sensor Microwave Imager (SSM/I) [ Judge et al , ; Jin et al , ; Kim et al , ], Advanced Microwave Scanning Radiometer–EOS (AMSR‐E) [ Zhao et al , ], and Advanced Microwave Scanning Radiometer 2 [ Hu et al , ] data have provided a way to produce a long‐term data record of near‐surface freeze/thaw state, since the availability of K a band allows these sensors to detect the surface temperature changes reliably. However, the indication for water phase transition of these sensors operating at C band or higher frequencies is weaker compared to the L band.…”
Section: Introductionmentioning
confidence: 99%